KARAKTERISTIK KALIGRAFI ARAB PADA MASJID ASMAUL HUSNA GADING SERPONG - Aprilyza, Aura Shifa; Rahman, Suranta Abdul (Multikultura, 2025)
Asmaul Husna Mosque in Gading Serpong uses the Asmaul Husna calligraphy design that decorates every outer wall of the mosque using Arabic calligraphy. This study aims to analyze the characteristics of the calligraphy used and the aesthetics and symbolic meanings contained in the calligraphy at the Asmaul Husna Mosque in Gading Serpong. This study uses a descriptive qualitative approach from data through printed and digital books, journals, newspapers, video documentation of the Asmaul Husna Mosque in Gading Serpong on certain platforms, as well as interviews with mosque administrators directly or indirectly as sources to maximize the results of research observations. The results of the study show that the Asmaul Husna Mosque in Gading Serpong has a unique design concept, namely the use of calligraphy with the words Asmaul Husna on every outer wall of the mosque. The Asmaul Husna calligraphy used at the Asmaul Husna Mosque in Gading Serpong is a Kufi Musattar calligraphy with stiff and angular characteristics. This design shows how elements of Islamic calligraphy art are integrated into the architecture of the mosque as a form of symbolism, Islamic identity of the place of worship, and cultural arts.